The Swiss Data Cube: Earth Observations for monitoring Switzerland's environment in space and time. Issue 1 (June 2020) - Giuliani, Gregory; Peduzzi, Pascal; Chatenoux, Bruno; Richard, Jean-Philippe; Poussin, Charlotte; Schaepman, Michael; Small, David; Steinmeier, Charlotte; Psomas, Achilleas; Ginzler, Christian
Abstract: Pressures on natural resources are increasing and a number of challenges need to be overcome to meet the needs of a growing population in a period of environmental variability. The key to sustainable development is achieving a balance between the exploitation of natural resources for socioeconomic development and maintaining ecosystem services that are critical to human's wellbeing and livelihoods. Some of these environmental issues can be monitored using remotely sensed Earth Observations (EO) data that are increasingly available from freely and openly accessible repositories. Hereafter, we present the Swiss Data Cube, a unique Analysis Ready Data archive of satellite imagery and some use cases to monitor Sustainable Development Goals.